2012
DOI: 10.4172/2168-9873.1000101
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Cutting Conditions in Multi-Pass Turning Using Hybrid Genetic Algorithm-Sequential Quadratic Programming

Abstract: IntroductionThe selection of optimal cutting parameters, like the number of passes, depth of cut for each pass, feed and speed, is a very important issue for every machining process [1]. Several cutting constraints must be considered in machining operations. In turning operations, a cutting process can possibly be completed with a single pass or by multiple passes. Multi-pass turning is preferable over single-pass AbstractIn this paper, a new, hybrid genetic algorithm-sequential quadratic programming is used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Basically, the idea was to switch fireflies with best values of objective function; actually, firefly's crossover is implemented. Firefly at position l, from population 1, replaces firefly at position k in population 2 and vice versa, firefly at position k from population 2 comes at position l in population 1 (Algorithm 2lines 36,37,38). This crossover of fireflies allows population with worse solutions to get into space of better solutions, while the population with better solutions checks if the global minimum is found, or there is even better solution to search for.…”
Section: Post Processing and Results Presentationmentioning
confidence: 99%
See 2 more Smart Citations
“…Basically, the idea was to switch fireflies with best values of objective function; actually, firefly's crossover is implemented. Firefly at position l, from population 1, replaces firefly at position k in population 2 and vice versa, firefly at position k from population 2 comes at position l in population 1 (Algorithm 2lines 36,37,38). This crossover of fireflies allows population with worse solutions to get into space of better solutions, while the population with better solutions checks if the global minimum is found, or there is even better solution to search for.…”
Section: Post Processing and Results Presentationmentioning
confidence: 99%
“…Belloufi et al. 37 used Firefly algorithm (FA) and hybrid genetic algorithm-sequential quadratic programming (GA-SQP) 38 and obtained lower numerical values of production cost compared with other techniques, but without satisfying all constraints. Srinivas et al.…”
Section: Literature Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The study concluded the EMO solutions were computationally faster than the original EMO results. Belloufi et al ( 2012 ) proposed a new hybrid algorithm with genetic and sequential quadratic programming procedures for a resolution of cutting conditions. The resolution of a multi-pass turning optimisation case was to minimise the production cost under a set of machining constraints.…”
Section: Introductionmentioning
confidence: 99%
“…Towards the search for the optimal solution, a great variety of algorithms has been proposed, either deterministic or stochastic ones, the first being easily trapped in local minima and the latter being very time consuming. The Langrange method, dynamic programming [4], fuzzy logic, the Taguchi technique [3,5], the cuckoo optimization algorithm [6], the particle swarm optimization algorithm (PSO) [7,8], the genetic algorithms (GA) [9,10], the hybrid teaching learning -based optimization (TLBO) [11] are only some of them.…”
Section: Introductionmentioning
confidence: 99%